How to cope with dengue in the developing countries like Pakistan? - Sohail, Filza; Alam, Gazi Mahabubul; Khan, Rizwan Rasul; Naeem, Rahmah (A N S I Network, 2011)
A viral disease like dengue lacking a specific form of treatment is a high menace to human health. Situation becomes worse in developing countries like Pakistan because of poor health care services and facilities. Using data from earlier works and analyzing them, this review aims to explore the disease epidemiology. Dengue Virus (DENV) destroys the immune system and causes health problems like headache, inflammation, bleeding, hypertension and mental disorders. Death also can be caused through dengue because of its adverse effects on liver which also may result in hepatitis. Dengue spread can be controlled through many ways like modulating the environment and devastating its vector. Biological control appears as potentila pproach to control its vector, especially the use of "Wolbachia". Currently, no vaccines are available against this virus and antiviral drugs are also not significantly effective. Phytochemical studies revealed that apple, papaya, lemon are rich source of carotenoids, esters, flavonoids, phenolic acid, terpene and vitamins. Apple was found to have a number of antiviral compounds like phytoestrogens, procyanidins and rosmarinic acid. Although there are few reports of antiviral compound obtained from papaya but it has been reported to have evocative beneficial effects on immune system. The phytochemicals behave as strong anti-oxidant and anti-inflammatory agents which can help the body against dengue-induced inflammation and oxidant stresses. Several other features are also found in these reviewed phytochemicals that can protects the human body from the adverse effects of dengue infection. In nutshell, the consuming of papaya and apple should be incorporated in daily routine life especially during the season when this disease appears in its epidemic form.